Mengukur Tingkat Perkembangan Kognitif Siswa Sekolah Dasar dalam Bidang Sains menggunakan Tes Kemampuan Penalaran Ilmiah - Prabowo, Chandra Adi; Widodo, Wahyu (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Students’ scientific reasoning abilities are influenced by many factors. The aim of the study is to determine the relationship between elementary students’ cognitive development with their gender, age, and academic achievement in science using Scientific Reasoning Skills Test. The subject of the study (N=140) were drawn from 5th and 6thgrade students of SDN Bareng 2 Malang. There were no significant relationship between students’ cognitive developments and their age and genders, a relationship was found with academic achievement in science.